Improving thermal conductivity of polymer composites by reducing interfacial thermal resistance between boron nitride nanotubes. (8th September 2018) - Fu, Chenjie; Li, Qiang; Lu, Jibao; Mateti, Srikanth; Cai, Qiran; Zeng, Xiaoliang; Du, Guoping; Sun, Rong; Chen, Ying; Xu, Jianbin; Wong, Ching-Ping
Abstract: Developing polymer composites with high thermal conductivity is a must to improve the thermal-management ability for modern electronic applications, in which power densities rapidly increase. Boron nitride nanotubes are one of the most promising fillers due to their high thermal conductivity and electrical insulator, but the overall thermal conductivity of the obtained polymer composites is limited by high interfacial thermal resistances. Here, we present an approach to reduce the interfacial thermal resistance between adjacent boron nitride nanotubes through low-melting effect of nanoscale silver particles. A sharp increase in thermal conductivity (20.9 Wm −1 K −1 ) is observed in cellulose nanofibers (CNFs)/boron nitride nanotubes (BNNTs) composites, which is approximately 14.3 times larger than that of conventional polymers. The underlying mechanism is understood through Foygel model, and demonstrated that the interfacial thermal resistances play key role in the thermal conductivity. This strategy can become a quotable method for design and prepared of highly thermal conductivity materials in the future.